2003
DOI: 10.1002/eji.200324241
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes during dendritic cell maturation correlate with cofilin activation and translocation to the cell membrane

Abstract: Upon activation, tissue residing immature dendritic cells (DC) start to migrate towards the draining lymph node and mature into efficient antigen-presenting cells. During maturation DC loose their capacity to endocytose antigens, change their surface expression of adhesion molecules, chemokine receptors, and costimulatory molecules, and change morphology. We employed 2D-PAGE and mass spectrometry to identify additional differentially expressed proteins in immature and mature DC. Human monocyte-derived DC were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 54 publications
2
64
1
1
Order By: Relevance
“…Interestingly, in the same study, cofilin was not enriched within the immunological synapse in B cells. However, Verdijk et al (42) reported translocation of cofilin toward submembranous regions in DCs in a stimulation-dependent manner, whereas we have observed an even distribution of cofilin within the cytosol of stimulated BMDCs (data not shown). Together, these findings suggest that cofilin may contribute to different degrees to immunological synapse formation in distinct APC populations.…”
Section: Discussioncontrasting
confidence: 71%
“…Interestingly, in the same study, cofilin was not enriched within the immunological synapse in B cells. However, Verdijk et al (42) reported translocation of cofilin toward submembranous regions in DCs in a stimulation-dependent manner, whereas we have observed an even distribution of cofilin within the cytosol of stimulated BMDCs (data not shown). Together, these findings suggest that cofilin may contribute to different degrees to immunological synapse formation in distinct APC populations.…”
Section: Discussioncontrasting
confidence: 71%
“…We plan to determine the significance of these cells using more advanced biochemical and immunological methods. Other than this anomaly, DCs from each source followed the expected progression of phenotype, supported by others (41). Immature DCs displayed long, thin dendritic processes, day 3 cells were a combination of veils and processes, mature DC displayed dense cytoplasmic veils on the cell surface, and day 10 cells were sparsely covered in veils.…”
Section: Discussionsupporting
confidence: 67%
“…We also noted a difference in nuclear size from day 0 to day 7 DCs, with the average nuclear size increasing as the DCs matured. This has been seen by others (39,41), and is due to an increase in cell size as a whole.…”
Section: Ultrastructure Of Developing Dendritic Cellssupporting
confidence: 70%
“…Scale bar, 20 µm. al., 1999;Nagata-Ohashi et al, 2004;Verdijk et al, 2004) Although cofilin still actively participated in membrane protrusion in both Du145-Mock and Du145-CD82 cells, Icouldn't determine whether cofilin is the primary driven force for membrane protrusion formation or not in this spectacular experiment. This is not a surprise to us as overexpression of cofilin may impair the actin cytoskeleton rearrangement and cell migration (Lee et al, 2005) or enhance the same process (Dang et al, 2006).…”
Section: Kai1/cd82 Blocks Cofilin Translocationmentioning
confidence: 97%
“…The two models are In addition to all these functions described above, the cofilin pathway contributes to morphogenesis, such as cell polarity in Drosophila (Blair et al, 2006), and blastocyst positioning and body wall formation . Driven by variety of stimuli, cofilin becomes dephosphorylated or activated, then translocated to the plasma membrane (Suzuki et al, 1995;Nagaishi et al, 1999;Nagata-Ohashi et al, 2004;Verdijk et al, 2004) where it interacts with the actin cytoskeleton and promotes actin cortical meshwork formation, actin recycling, and consequently lamellipodia formation (Raftopoulou and Hall, 2004).…”
Section: Crosstalk Among Rho Gtpasesmentioning
confidence: 99%